Quality of life and nutritional status of institutionalized and non-institutionalized elderly (Research, Society and Development, 2021)
Objective: To associate the domains of quality of life with institutionalized and non-institutionalized elders’ nutritional state and age in Long Stay Institutions for the Elderly. Methodology: This study is retrospective, transversal, and quantitative developed with 105 non-institutionalized assisted by a Family Health Strategy (FHS) in Lajeado and 245 institutionalized elders, who live in private and public Long Stay Institutions for the Elderly (LSIEs) both in Rio Grande do Sul. We used the World Health Organization Quality of Life Questionnaire (WHOQOL-bref), which is composed by 26 questions with a hedonic scale from 1 to 5. We assessed the elder’s weight and height in order to determine the body mass index (BMI) and to classify their nutritional state according to Pan American Health Organization (2002). We consider as significant the results with a significance level of 5%. Results: The higher score of elders’ quality of life was noticed in the psychic domain 45±27,53, followed by the environmental 41,46±18,23, social 40,82±30,68 and physical 39,28±20,10 being the domains of quality of life significantly superior among the elders from 60 to 90 years (p≤0,01), the ones with nutritional state classified as obesity (p≤0,01) and the non-institutionalized when compared to the institutionalized ones. Conclusion: The perception of the studied domains of quality of life was higher in the psychic than in the physical domain. The younger elders, the ones with obesity and the non-institutionalized showed a better perception of quality of life in all the domains.